Evaluating the effect of a pilot drought policy measure on farmer practices and behaviour - Heath, Rebecca Tammy (Curtin University, 2017)
This thesis examined the influence of a pilot drought policy program on the capacity, behaviours and resilience of farm businesses. The program had mixed effects on capacity levels, but supported the development and implementation of holistic strategic plans. Continued use of the plans was uncertain. Consequently, the contribution of the program to farm business resilience was tenuous, with tension between the process used by the program to develop strategic plans and the overarching policy objectives.